The cure for what ales you - Alexander, Ellie (Alexander, Ellie. Sloan Krause mysteries, 2021)
"Amateur sleuth and brewer Sloan Krause contends with her past--and a murder related to it--in The Cure for What Ales You, another delightful mystery from cozy writer Ellie Alexander..."--